Status Kemampuan Motorik Umum Siswa Sekolah Sepak Bola di Kabupaten Sleman - Setyo Nugroho (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2006)
The descriptive survey is intended to measure the General Motor Ability (GMA) of soccer school students. Involving 227 junior high school students, the study employed GMA test consisting of test in standing broad jump, zigzag run, and medicine ball put. Test results were analyzed using Barrow's T-score, resulting in the findings that overall 17% of the students were categorized as good players, 71% as average, and 12% as poor.